Comparison of non-contrast CT vs. contrast-enhanced CT with both intravenous and rectal contrast application for diagnosis of acute colonic diverticulitis: a multireader, retrospective single-center study - Móré, Dorottya; Erdmann, Stella; Bischoff, Arved; Wagner, Verena; Kauczor, Hans-Ulrich; Liesenfeld, Lukas; Abbasi Dezfouli, Katharina; Giannakis, Athanasios; Klauß, Miriam; Mayer, Philipp (Diagnostics, 2025)
Objectives: To evaluate the non-inferiority of non-contrast CT compared to contrast-enhanced CT with both intravenous and rectal contrast application for the diagnosis of acute colonic diverticulitis. Methods: Five readers retrospectively evaluated the non-contrast and contrast-enhanced series of CTs of 205 consecutive patients with clinical suspicion of acute diverticulitis. Two randomized reading sessions, both containing all 205 cases as either contrast-enhanced or non-contrast (1:1) series, were performed with >= 8 weeks washout between them. The non-inferiority margin was set to 0.1. Results: The pooled prevalence (all readers) of diverticulitis was similar for non-contrast CT (63.9%, range: 60.5-65.0%) and contrast-enhanced CT (64.4%, 61.5-67.8%). Non-contrast CT was non-inferior for the diagnosis of diverticulitis (accuracy 0.90 [95% confidence interval: 0.89, 0.92]) compared to contrast-enhanced CT (0.92 [0.90, 0.94]; the difference in accuracy: -0.01 [-0.04, 0.01]) (normal deviate test: p-valueone-sided = 5.20 x 10-6). Sensitivities for perforation and abscess were slightly but significantly lower for the non-contrast CT than for the contrast-enhanced CT (differences: -0.15 [-0.20, -0.05], -0.17 [-0.27, -0.07]), while no differences in accuracies and specificities were observed. Conclusions: Non-contrast CT is non-inferior to contrast-enhanced CT (intravenous and rectal contrast) for the diagnosis of acute colonic diverticulitis. Contrast-enhanced CT is associated with significantly higher sensitivities for the presence of an abscess or perforation.